Establishment of Sustainability through Open Access to Research Infrastructure in a Calibration Laboratory for Extreme Electrical Metrology - Cundeva-Blajer Marija (EPJ Web of Conferences)
The laboratory sustainability aims at reducing environmental impacts of laboratory activities, like energy and water use, waste production, and greenhouse gas emissions, benefitting in cutting costs, improving laboratory reputation, supporting the UN SDGs of environmental protection, social justice, collaboration among laboratory staff and stakeholders. This can be achieved by inclusiveness and openness of the laboratory infrastructure towards different users, through defined procedure of “open access” to the laboratory research infrastructure. The sustainability measures implementation in the Laboratory for Electrical Measurements (LEM) at the Ss. Cyril and Methodius University in Skopje, is described. It is a calibration laboratory for instruments for electrical quantities, accredited according to EN ISO/IEC 17025:2017. The LEM sustainability maturity evaluation, through mapping and gap analysis is presented, enabling creation of strategic documents like the Quality and Sustainability Policy, Quality and Sustainability Manual and the Access Policy to the Research Infrastructure. Conflicting issues arise between openness and confidentiality, but these challenges are overcome. Two outputs are delivered by deploying risk-based thinking: 1) successful extension of the LEM accreditation scope in calibration of extreme electrical quantities, complying with EN ISO/IEC 17025:2017, including the point 4.2 (confidentiality requirements), and 2) strategic documents adoption, imposed by public funding conditions.